An Econometric Model for the Oil Dependence of the Russian Economy - Perifanis, Theodosios; Dagoumas, Athanasios (International Journal of Energy Economics and Policy, 2017)
There is lot of discussion on the level of the oil dependence of the Russian economy, as well as on whether the Russian Federation presents signs of the Dutch disease or even if already suffers by it. In this paper, we develop econometric models for examining the oil dependence of the Russian economy. We construct two VARs and then we proceed with VECMs models. The models consider macroeconomic factors, such as industrial production index, unemployment, GDP and government expenditure, as well as oil factors, such crude oil price and Russian oil production. We employ impulse response functions to catch the interactions among variables. We find strong evidence on the oil dependence of the Russian economy; however, we do not find firm established proof of the Dutch disease. Keywords: Russia, oil, cointegration JEL Classifications: Q43, C01, P48